Improving the sustainability performance of Western Australian house construction: A life cycle management approach - Lawania, Krishna Kumar (Curtin University, 2016)
Addressing sustainability is a major issue for Australian building sector as it is responsible for 20% of total energy consumption and 23% of GHG emissions. This research has developed a comprehensive life cycle management framework that integrates the NatHERS energy rating tool, life cycle assessment, cleaner production strategies, life cycle costing, and socio-political factors for improving the sustainability performance of construction of houses in Western Australia.